(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The aim of the study was to assess how agricultural teachers view the importance of agricultural mechanization within the agricultural education curriculum in secondary schools in Zuru Local Government, Kebbi State. Four research objectives with correspondent research questions were formulated to guide the study. A descriptive survey research design was adopted. Ten (10) secondary schools were purposely selected for the study across the study areas out of which two (2) were private schools. Simple random sampling technique was used to select one hundred (100) agricultural science teachers from the sampled schools. Questionnaire with four point rating scale was used to elicit responses from the respondents. Data were analyzed using descriptive statistics of mean and standard deviation. The results revealed a positive perception held by secondary school teachers regarding the concepts in agricultural mechanization education with the overall mean of 3.52 that was above the 2.50 cut of point on a four point rating scale among others. Based on the findings, it is recommended that efforts should be made to improve agricultural mechanization curriculum by incorporating the rejected instructional areas, training workshops and capacity-building programs should be organized for secondary school teachers to deepen their understanding and ability to teach mechanized farming concepts effectively.